Correlations of university students' feelings during the COVID-19 pandemic with academic adaptation and quality of life - Carneiro, Priscilla Rodrigues Caminha; Oliveira Silva, George; Aredes, Natália Del Angelo; Bittencourt, Margarete Carréra; Quaresma, Fernando Rodrigues Peixoto; Nascimento, Ladislau Ribeiro do (Frontiers in Education, 2024)
This study aimed to identify the feelings experienced by university students during the Covid-19 pandemic and its correlation with academic adaptation and quality of life (QoL). Through a cross-sectional and correlational design, 90 university students completed a questionnaire about feelings, academic adaptation, and QoL during the pandemic. Spearman's correlation was used to identify the correlation between the feelings and the academic adaptation, and quality of life.Multiple linear regression models were used to identify the predictors feelings of academic adaptation and the physical and mental components of the quality of life. Good academic adaptation as well as good QoL scores were identified in the sample. During the pandemic period, students experienced feelings of exhaustion, discouragement, irritation, exhaustion, insecurity, drowsiness, anxiety, worry and tiredness with greater intensity. Positive feelings were reported as well, such as with energy and willing. The feelings could predict variations in academic adaptation, physical and mental health. Additionally, was identified greater correlation of feelings with the QoL domains related to the individual's perception of mental health. The results of this study highlight that, in the context of public health emergencies, investments are needed in institutional policies to support students, to avoid difficulties in academic adaptation that impact dropout, as well as to avoid the emergence/worsening of disorders such as anxiety and depression.